Non-metric dental analysis of a Bronze Age population from the Armenian Plateau - Khudaverdyan, Anahit Yu. (Anthropological Review, 2013)
The aim of this study is to assess the biological distance between populations from the Armenian highland, Georgia, Eastern Europe, Central Asia and Siberia on the basis of the frequency of non-metric dental traits. It is well known that these traits are characterized by high inter-population differentiation, low sexual dimorphism, and their recording is affected by relatively small intra and inter-observer error. These traits are successfully used in the description and explanation of ethno-genetic processes. Comparative analysis was performed on 30 populations, and the frequency of non-metric dental traits in all populations was determined by principal component analysis. Based on our bio-distance results, we suggest there was a degree of genetic proximity among inland populations of the Armenian Plateau and Transcaucasian area at the beginning of the Bronze Age. The Armenian Plateau and Georgian samples and all those from Kalmykia (Pit Grave culture), the Ukraine (Tripolye culture), the Urals (Sintashtinskaya, Timber Grave cultures), the Volga region (Pit Grave, Balanovo, Fatianovo, Potapovsky cultures) and Central Asia (Gonur-Depe) exhibited close affinities. This conclusion is consistent with that reported by other bio-distance studies examining non-metric cranial traits and Armenian Plateau samples.